2016
DOI: 10.1111/odi.12564
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants and postorthodontic external apical root resorption in Czech children

Abstract: Although the effect of individual SNPs studied on the EARR development was not confirmed in the Czech population, complex analysis suggested that variability in the P2RX7 gene and the length of orthodontic treatment may be important factors contributing to the etiopathogenesis of postorthodontic EARR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
22
2
Order By: Relevance
“…Various research groups studied the single nucleotide polymorphisms (SNPs) in the OPN coding gene Spp1 and its effect on the tooth root resorption [ 58 60 ]. Iglesias-Linares and coworkers first reported that OPN gene SNPs (rs9138, rs11730582) are involved in the susceptibility of external root resorption in patients undergoing orthodontic treatment [ 58 ].…”
Section: Opn-mediated Tooth Root Resorption and Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Various research groups studied the single nucleotide polymorphisms (SNPs) in the OPN coding gene Spp1 and its effect on the tooth root resorption [ 58 60 ]. Iglesias-Linares and coworkers first reported that OPN gene SNPs (rs9138, rs11730582) are involved in the susceptibility of external root resorption in patients undergoing orthodontic treatment [ 58 ].…”
Section: Opn-mediated Tooth Root Resorption and Repairmentioning
confidence: 99%
“…Iglesias-Linares and coworkers first reported that OPN gene SNPs (rs9138, rs11730582) are involved in the susceptibility of external root resorption in patients undergoing orthodontic treatment [ 58 ]. However, in another study, OPN gene SNPs and its effect on external apical root resorption (EARR) were not confirmed in Czech children [ 60 ]. However, the association between individual variability in purinoreceptor (P2X7) and EARR was suggested to be an important factor in the etiopathogenesis of EARR [ 60 ].…”
Section: Opn-mediated Tooth Root Resorption and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider imperative to recognize the epigenetic modulation on coding and noncoding chromosomal regions that influence our proteome, resulting on a dynamic molecular effect rather than a static picture of our protein map. Thus, genotyping our patients represent only one piece of this complex puzzle [40][41][42][43][44][45] . Nonetheless, this type of particular responses associated with the speed of tooth movement, being mediated dynamic genetic characteristics, could generate different functional phenotypes in the population.…”
Section: Discussionmentioning
confidence: 99%
“…EARR is a common phenomenon after orthodontic treatment. 23 30 31 Therefore, assessing the risk of developing EARR after orthodontic treatment is an important factor for successful treatment. Progression of EARR is a multifactorial event.…”
Section: Discussionmentioning
confidence: 99%